2020
DOI: 10.3390/vaccines8030547
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Canine Parvovirus Vaccination in Dogs with Hyperadrenocorticism Treated with Trilostane

Abstract: It is unknown how dogs with hyperadrenocorticism (HAC) respond to vaccination. This study measured antibodies against canine parvovirus (CPV) in dogs with HAC treated with trilostane before and after CPV vaccination, and compared the immune response to that from healthy dogs. Eleven dogs with HAC, and healthy age-matched control dogs (n = 31) received a modified-live CPV vaccine. Antibodies were determined on days 0, 7, and 28 by hemagglutination inhibition. Univariate analysis was used to compare the immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…To the best of our knowledge, there are no available studies on vaccine response in patients with endogenous GC excess. In dogs with hyperadrenocorticism treated with trilostane, the immune response to canine parvovirus vaccination was comparable with that of healthy dogs [106].…”
Section: Glucocorticoids and Sars-cov-2 Mrna Vaccinesmentioning
confidence: 76%
“…To the best of our knowledge, there are no available studies on vaccine response in patients with endogenous GC excess. In dogs with hyperadrenocorticism treated with trilostane, the immune response to canine parvovirus vaccination was comparable with that of healthy dogs [106].…”
Section: Glucocorticoids and Sars-cov-2 Mrna Vaccinesmentioning
confidence: 76%
“…Furthermore, thyroid hormones can affect endogenous glucocorticoid levels [ 22 , 23 , 24 ]. The administration of triiodothyronine (T3) and T4 suppressed the basal and ACTH-stimulated levels of blood cortisol, at least in rats [ 23 ]; in contrast, low levels of thyroid hormones could lead to a chronic elevation of endogenous blood cortisol and thus impaired immune function [ 22 ], although a previous study revealed that the immune response of dogs with treated hyperadrenocorticism (HAC) to MLV vaccination against CPV was not significantly impaired in comparison to that of healthy dogs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has been made in developing diagnostics [ 27 , 28 , 29 , 30 , 31 ], vaccines [ 29 , 32 , 33 , 34 ], and treatment protocols [ 3 , 35 , 36 , 37 , 38 ] for canine parvovirus (CPV) since its emergence, few methodologies have been developed to attempt to limit or slow the spread of this disease within vulnerable populations. This may be partially due to a belief that reductions like this are not possible, given the extensive period during which CPV can survive in the environment [ 4 ] and difficulty in disinfecting CPV-infected areas (i.e., dog parks, homes, shelters, etc.)…”
Section: Discussionmentioning
confidence: 99%